2021
DOI: 10.1002/admt.202100289
|View full text |Cite
|
Sign up to set email alerts
|

All Solid‐State Flexible Electrochromic‐Organic Light‐Emitting Diode Devices on Single‐Plastic Substrate for See‐Through Display Technologies

Abstract: modulation of its transmittance states. The basic unit of an EC device consists of an electrolyte layer and two symmetric EC electrodes: cathodic and/or anodic EC film deposited on a conductive and transparent substrate. Upon application of an external potential the EC materials can undergo reversible changes of their optical absorption by redox processes and the simultaneous insertion/extraction (coloration/ decoloration) of charge-balancing ions. [10] With regard to the fabrication methods, the most part of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Interestingly, we observed that direct vacuum deposition of WO 3 on a soft polymer substrate (Nafion) enabled the random packing of the WO 3 clusters playing a key role in the WO 3 pillar-like growth and the consequent structuring of the hybrid nanocomposite film. Recently, apart from demonstrating the integration of such a novel device with other optoelectronic units on a single substrate , and the scale-up on a large area, , we contextually observed that the introduction of different buffer layers at the anode consisting of ultrathin films of TiO 2 or SiO 2 , respectively, can effectively result in the cycling stability of this monolithic single-substrate device. , …”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Interestingly, we observed that direct vacuum deposition of WO 3 on a soft polymer substrate (Nafion) enabled the random packing of the WO 3 clusters playing a key role in the WO 3 pillar-like growth and the consequent structuring of the hybrid nanocomposite film. Recently, apart from demonstrating the integration of such a novel device with other optoelectronic units on a single substrate , and the scale-up on a large area, , we contextually observed that the introduction of different buffer layers at the anode consisting of ultrathin films of TiO 2 or SiO 2 , respectively, can effectively result in the cycling stability of this monolithic single-substrate device. , …”
Section: Introductionmentioning
confidence: 99%
“…Another fundamental and critical aspect for the realization of highly durable solid-state devices lies in the choice of the electrolyte component because it plays a pivotal role in the structural features and the overall stability of the device. Among the different types, solid polymer electrolytes (SPEs) have gained major expectations for their potential advantages, among which are the wide electrochemical window, ease of processability, low cost, and low interfacial resistance over inorganic ceramic electrolytes. They also guarantee outstanding features of no leakage, high flexibility, light weight, and good compatibility with electrode materials, making them suitable for scale-up to a large area and for the integration with other optoelectronic units, such as a photovoltaic cell or organic light-emitting diode . However, SPEs generally suffer from lower conductivity than the liquid or gel counterparts, and most SPEs and gel electrolytes can be involved in degradative processes promoted by parasitic side reactions with air or moisture or subjected to photo-oxidative degradation by UV radiation or catalytic processes with the consequent discoloration of the surface and extensive mechanical damages, thus compromising their aesthetic and functional requirements.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations